PENANAMAN SIKAP SOSIAL MELALUI PEMBELAJARAN IPS PADA PESERTA DIDIK KELAS V/A MI QUBA KOTA SORONG - Muhammad Ramli; Umar Sulaiman; Nurhikmah Nurhikmah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2021)
In current conditions, educational problems occur due to the increasing number of things and factors that influence the development of students' social attitudes. Therefore, it is the task of educators to save and maintain the value of their social attitudes through social studies learning because they are physically and psychologically different. This study uses a qualitative type. In this study, the researchers took the place/location carried out at MI Quba, Sorong City. The research approach used is a combination. In this case, Nasution stated, “The analysis has started since formulating and explaining the problem, before going into the field, and continuing until the writing of research results. Cultivating Social Attitudes Through Social Studies Learning in Class V/A Students of MI Quba Sorong City can be instilled through social studies learning by instilling the values ​​of social attitudes in students with social studies learning strategies, the teacher's ability to provide examples of good interaction attitudes to students in the classroom. Results of Implanting Social Attitudes in Class V/A Students Through Social Studies Learning for Class V/A Students at MI Quba Sorong City has been embedded with the